2009
DOI: 10.1002/jmri.21822
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of dGEMRIC in assessment of hip joint cartilage: A prospective study

Abstract: Purpose:To investigate the reproducibility of dGEMRIC in the assessment of cartilage health of the adult asymptomatic hip joint. Materials and Methods:Fifteen asymptomatic volunteers (mean age, 26.3 years Ϯ 3.0) were preliminarily studied. Any volunteer that was incidentally diagnosed with damaged cartilage on MRI (n ϭ 5) was excluded. Ten patients that had no evidence of prior cartilage damage (mean age, 26.2 years Ϯ 3.4) were evaluated further in this study. The reproducibility of dGEMRIC was assessed with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 24 publications
0
37
1
1
Order By: Relevance
“…Bittersohl et al proved this technique to be a reliable instrument in the assessment of asymptomatic hip joint cartilage. 117 In a pilot study Bittersohl et al proved the feasibility of cartilage assessment in symptomatic FAI patients using intra-articular delayed Gadolinium Enhanced MRI of Cartilage (iadGEMRIC). 118 In another study Bittersohl et al 119 found that mapping with both ivdGEMRIC and ia-dGEMRIC demonstrated obvious differences between various grades of cartilage degeneration.…”
Section: Mri Appearance Of Normal and Pathologic Featuresmentioning
confidence: 99%
“…Bittersohl et al proved this technique to be a reliable instrument in the assessment of asymptomatic hip joint cartilage. 117 In a pilot study Bittersohl et al proved the feasibility of cartilage assessment in symptomatic FAI patients using intra-articular delayed Gadolinium Enhanced MRI of Cartilage (iadGEMRIC). 118 In another study Bittersohl et al 119 found that mapping with both ivdGEMRIC and ia-dGEMRIC demonstrated obvious differences between various grades of cartilage degeneration.…”
Section: Mri Appearance Of Normal and Pathologic Featuresmentioning
confidence: 99%
“…As a next imaging modality, CT-especially in combination with dynamic computerized analysis-enables excellent visualization of the three-dimensional osseous anatomy ( 30,42 ). This could enhance understanding of the underlying hip disease in a patient and sensitize the treating physician so that he or she could recognize the importance of subtle deformities.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their negative charge, glycosaminoglycans repulse the negatively charged contrast agent; thus, in areas with depleted glycosaminoglycan concentration, an accumulation of contrast material can be detected [49]. Already established in knee research [50,51], these observations were reproduced in the hip [52]. However, an IV injection of gadopentetate dimeglumine is A B required followed by temporary exercise to distribute the gadolinium.…”
Section: Compositional Imagingmentioning
confidence: 99%